Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health status of minority Francophone seniors in Manitoba and access to services in french: Potential for social isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ethier, Sophie (Human Development, Disability, and Social Change, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed. Keywords: seniors, health, Francophone minority, home care

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.